2014
DOI: 10.1155/2014/640291
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity and Occurrence of Fetal Macrosomia: A Systematic Review and Meta-Analysis

Abstract: Objective. To determine a precise estimate for the contribution of maternal obesity to macrosomia. Data Sources. The search strategy included database searches in 2011 of PubMed, Medline (In-Process & Other Non-Indexed Citations and Ovid Medline, 1950–2011), and EMBASE Classic + EMBASE. Appropriate search terms were used for each database. Reference lists of retrieved articles and review articles were cross-referenced. Methods of Study Selection. All studies that examined the relationship between maternal obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
177
0
20

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(210 citation statements)
references
References 281 publications
(38 reference statements)
13
177
0
20
Order By: Relevance
“…In addition, obesity rates are high in these regions (119), and obesity has been shown to be associated with low vitamin B-12 (79,(120)(121)(122). The link between obesity, gestational diabetes, and low vitamin B-12 concentrations has not been fully explored, but because the former 2 conditions are independently associated with fetal macrosomia, they may partly compensate for or mask the associations between vitamin B-12 and LBW (123,124).…”
Section: B-12 Insufficiency In Pregnancy and Birth Weightmentioning
confidence: 99%
“…In addition, obesity rates are high in these regions (119), and obesity has been shown to be associated with low vitamin B-12 (79,(120)(121)(122). The link between obesity, gestational diabetes, and low vitamin B-12 concentrations has not been fully explored, but because the former 2 conditions are independently associated with fetal macrosomia, they may partly compensate for or mask the associations between vitamin B-12 and LBW (123,124).…”
Section: B-12 Insufficiency In Pregnancy and Birth Weightmentioning
confidence: 99%
“…Many studies have demonstrated that maternal obesity results in fetal overgrowth [1, 5, 3840] and increases the risk for obesity later in life [4]. Dietary interventions that focused on calorie and glycemic control during pregnancy improved maternal metabolism but often failed to translate into improved fetal growth outcomes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Both higher maternal pregnancy BMI and increased gestational weight gain are well-known risk factors for larger sizes of gestational age infants. A meta-analysis among 13 that, as compared to normal maternal pre-pregnancy weight, maternal pre-pregnancy obesity was associated with a 2-fold higher risk of delivering larger sized gestational age infants [17] . Similarly, a meta-analysis among 15 cohort and case-control studies showed that excessive gestational weight gain based on the IOM criteria was associated with a 2-fold higher risk of macrosomia [18] .…”
Section: Fetal Outcomesmentioning
confidence: 99%